3D hierarchical porous N-doped carbon aerogel from renewable cellulose: an attractive carbon for high-performance supercapacitor electrodes and CO2 adsorption. Issue 19 (8th February 2016) - Hu, Yijie; Tong, Xing; Zhuo, Hao; Zhong, Linxin; Peng, Xinwen; Wang, Sha; Sun, Runcang
Abstract : 3D hierarchical porous N-doped carbon aerogel from renewable cellulose: an attractive carbon for high-performance supercapacitor electrode and CO2 adsorption. Abstract : Hierarchical porous N-doped carbons have attracted great interest in energy storage and CO2 capture applications due to their unique porous structure and physicochemical properties. Fabrication of cost-effective and eco-friendly hierarchical porous N-doped carbons from renewable biomass resources is a sustainable route for future energy storage. However, it is still a big challenge to produce N-doped carbons with hierarchical porous structure from cellulose, which is the most abundant and widely available renewable resource on earth. Here, we designed a facile and effective strategy to produce hierarchical porous N-doped carbons from cellulose for high-performance supercapacitor and CO2 capture applications. In this method, hierarchical porous cellulose aerogels were first obtained via a dissolving–gelling process and then carbonized in NH3 atmosphere to give hierarchical porous N-doped carbon aerogels with more interconnected macropores and micropores. Due to the unique porous structure and physicochemical properties, the as-prepared N-doped carbon aerogels had a high specific capacitance of 225 F g −1 (0.5 A g −1 ) and an outstanding cycling stability. For the first time, we also demonstrated that this N-doped carbon aerogel exhibited a exceptional CO2 adsorption capacity of 4.99 mmol g −1, which is much higher than those of other porous carbons. This novel hierarchical porous N-doped carbon has great potential applications in CO2 capture, energy storage, porous supports, and electrochemical catalysis.